Analysis of Hospital management information systems using cobit 5 framework case study "Saraswati Dental and Oral Hospital in Denpasar” - Raditya Pramita, I Putu Agus; Indrawan, Gede; Setemen , Komang (Bulletin of Social Informatics Theory and Application, 2023)
A hospital's operations, such as patient registration, medical management, financial management, and upgrading the services offered in the hospital, are managed and organized using an application system called a hospital management information system (HMIS). Because the lack of evaluation in the usage of HMIS has led to insufficient security in the HMIS, this research focuses on Saraswati Dental and Oral Hospital as the research site. Due to lax security measures, confidential data is readily accessible. The prevalence of duplicate data entry is an issue, and the success of HMIS performance implementation is still unknown. The COBIT 5 framework has been used to administer the HMIS at Saraswati Dental and Oral Hospital using the MEA (Monitor, Evaluate, Assess) and BAI (Build, Acquire, Implement) domains in response to these problems. This decision was made with the intention of aligning the application with the necessary features, monitoring system security, evaluating, and assessing the domain's alignment with the hospital's strategy in order to ascertain whether the current system still achieves the intended goals and maintains the controls required to satisfy the requirements. This study makes use of questionnaire, observation, and interview techniques. The capacity levels used in the COBIT 5 study were taken from ISO/IEC 15504-2-2003, and they were combined using straightforward mathematical calculations in accordance with the rules for computing capability values. Weaknesses or flaws in the security system that need to be fixed can be found by analyzing the capability levels in the MEA and BAI domains. The study's findings include suggestions for increasing the security system, which will enhance Saraswati Dental and Oral Hospital's HMIS performance and give users and patients with more beneficial outcomes